The improvement of coordination abilities of young gymnasts aged 7-8 years - Mulligildina A.Ya; Deyneko A.Kh; Krasova I.V (Kharkov National Pedagogical University, 2012)
The article presents the substantive training in gymnastics by young gymnasts aged 7-8 years, the improvement of coordination abilities of gymnasts through simultaneous work with two balls is highlighted. The research has involved 20 young gymnasts and the experimental group had 10 people. The level of coordination abilities of gymnasts is underpinned, the comparative analysis of subject possession by the right and the left hand is stressed. The method of studying with two balls aimed on the development of athletes sensorimotor coordination is pointed out in the article. The authors obtain significant changes in the coordination abilities of experimental group gymnasts, a positive impact on the preparation of other events is demonstrated.